LinTraP: Primitive Operators for the Execution of Model Transformations with LinTra - Burgueño-Caballero, Lola; Syriani, Eugene; Wimmer, Manuel; Gray, Jeff; Vallecillo-Moreno, Antonio Jesús (My University, 2014)
The problems addressed by Model-Driven Engineering (MDE) approaches are increasingly complex, hence performance and scalability of model transformations are gaining importance. In previous work, we introduced LinTra, which is a platform for executing out-place model transformations in parallel. The parallel execution of LinTra is based on the Linda coordination language, where high-level model transformation languages (MTLs) are compiled to LinTra and eventually executed through Linda. In order to de ne the compilation modularly, this paper presents a minimal, yet su cient, collection of primitive operators that can be composed to (re-)construct any out-place, unidirectional MTL.
Keywords: Lenguajes de programación; Model Transformation; Linda; LinTra